Political Connections, Business Groups and Innovation - Simon Commander; Saul Estrin; Thamashi De Silva (Institute of Labor Economics (IZA), 2023)
It has been argued that Asia's remarkable economic achievements of the past 50 years build on institutional arrangements very different from the West, notably the central role of business groups (BGs). As Asian economies move from extensive to intensive growth, we enquire whether the business group organsational format will be as effective going forward. We argue that the ubiquity of BGs has been associated with the accretion of major market power, as well as overall concentration. Our empirical work, drawing on a sample of more than 9000 Asian firms, finds that while BGs are more innovative than non-affiliates, this is unsurprising given their access to additional resources. However, when we look at innovation at the country level, we find that the wider consequences of BGs on innovation may be negative.
Keywords: L22; O30; O53; 330; innovation; R&D; Asian business groups; market power; overall concentration